2004
DOI: 10.1023/b:jofl.0000039348.74270.03
|View full text |Cite
|
Sign up to set email alerts
|

Macrocycle-Derived Functional Xanthenes and Progress Towards Concurrent Detection of Glucose and Fructose

Abstract: The detection of saccharides in biological media is of great current importance for the monitoring of disease states. We have previously reported that solutions of boronic acid-functionalized macrocycles form acyclic oligomeric materials in situ. The oligomers contain fluorescent xanthene moieties. Current efforts are aimed at modulating the spectroscopic responses of these materials for the analysis of specific sugars. We describe conditions whereby the xanthene boronic acids exhibit high colorimetric fructos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…The maximum wavelength for reducing sugar measurements obtained at λ 494 nm. Rusin et al describe for detecting glucose can be done at a wavelength in the UV-Vis Region 460 -530 nm [26]. The maximum wavelength spectrum for reducing sugar measurements presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum wavelength for reducing sugar measurements obtained at λ 494 nm. Rusin et al describe for detecting glucose can be done at a wavelength in the UV-Vis Region 460 -530 nm [26]. The maximum wavelength spectrum for reducing sugar measurements presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The boronic acids, which recognize cis-diol configuration in saccharides and form reversible covalent complexes in aqueous media, represent an ideal synthetic molecular receptor having the ability to selectively recognize saccharides [14][15][16]. Phenylboronic acid derivatives have been developed for saccharide sensing in various methods based on piezoresistive microcantilevers [17], UV-vis absorption [18][19][20][21][22][23][24], fluorescence [22,[25][26][27][28][29][30], electrochemistry [31][32][33][34], plasmonics [35][36][37], holography [38][39][40]. Consequently, boronic acids can be used as the recognition moiety for detecting saccharides in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence spectroscopy is one of the most powerful and widely used methods in studying the enantioselectivity of several biological systems because of its relatively high sensitivity, selectivity, and versatility. [18][19][20][21] Consequently, enantioselective fluorescent sensors have attracted considerable interest for use in potential bioanalytical applications. [22][23][24] When enantioselective studies are performed in an achiral environment, chiral discrimination is not observed.…”
Section: Introductionmentioning
confidence: 99%